Callisia fragrans (Lindl.) Woodson, a Little Known Succulent in Cuba - Isidro E. Méndez Santos (Agrisost, 2020)
Context: The presence of Commelinaceae plants in a park in the city of Camagüey, which does not correspond to any species of this family previously recorded in Cuba, created the need to study its identity, origin, and properties.